The Effect of adding Coconut Shells and Corn Husk to Biobriquettes from Fish Bone Waste - Nindyapuspa, Ayu; Setiani, Vivin; Firnanda, Dhea Ayu (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Biomass generates a large amount of waste. One of these is fish bones, corn husks, and coconut shells. Fish bone waste has the potential to be used as biobriquettes because it contains 10.16% carbon. To maximize the potential of fish bone waste, it should be mixed with corn husks and coconut shells. In addition, more calories can be added to the biobriquettes.  In the manufacture of biobriquettes, pyrolysis temperature also affects the quality of the resulting biobriquettes. The purpose of this study was to determine the quality of biobriquettes with a mixture of fish bones, corn husks, and coconut shells at 5000C and 3500C. The compositions of the biobriquette materials used in this study were 100% fish bone waste, fish bone:coconut shell waste (50:50), and fish bone waste:corn husk (50:50). The results of the study showed that biobriquettes with a mixture of fish bones and coconut shell 50:50 at a pyrolysis temperature of 350 °C had the best quality according to SNI 01-6235-2000 concerning wood charcoal briquettes. The water content and calorific value were 1.93% and 5,913.6 cal/g, respectively. The addition of coconut shells and corn husks affected the characteristics of biobriquettes made from fish bone waste.